The Role of Strategic Flexibility in Achieving Organization Effectiveness: Analytical Research in the Directorates of the Ministry of Education - Abdul Hussein, Sarah Hussein; Salman, Saadoon Muhsin (Journal of Economics and Administrative Sciences, 2022)
This research aims to know the role of strategic flexibility in achieving organizational effectiveness by studying the dimensions of strategic flexibility (capacity flexibility, resource flexibility, information flexibility, and coordination flexibility) on the dimensions of organization effectiveness (environmental adaptation, productivity and achieving goals) through an analytical study conducted in six directorates in the office of the Iraqi Ministry of Education. The research problem was represented in the form of questions, the most prominent of which was "What is the role of strategic flexibility in achieving organization effectiveness?" The descriptive analytical approach was relied on in applying the research, as the questionnaire was used as a tool for data collection and was prepared using ready-made standards, and the questionnaire was distributed to a sample of (131) individuals in (6) directorates in the Ministry of Education. The sample top management senior and middle represented by (general manager, assistant general manager, department manager, assistant department manager, division official), as the researcher used the five-point Likert scale to determine the answers to the paragraphs of the questionnaire, and then the data was analyzed and hypotheses tested using statistical tools and methods and analyzed using ready-made statistical programs(SPSS-V28) and (Excel 2010) to extract the results. Through the results, it is clear that there is a role of strategic flexibility in its dimensions (capabilities flexibility, resources flexibility, information flexibility and coordination flexibility) in achieving organization effectiveness